2006
DOI: 10.1055/s-2006-924320
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor Binding Protein-2 (IGFBP-2) is a Marker for the Metabolic Syndrome

Abstract: Low IGFBP-2 is associated with multiple cardiovascular risk factors similarly to IGFBP-1. Such associations were not apparent for IGFBP-3. Lack of marked prandial regulation of IGFBP-2, in contradistinction to IGFBP-1, may make IGFBP-2 a more robust biomarker for identification of insulin-resistant individuals at high cardiovascular risk in epidemiological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
91
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 22 publications
15
91
2
1
Order By: Relevance
“…When we silenced FASN in the PCa cells, however, we found no reduction in the protective effect conferred by hyperglycaemia (in contrast to the amelioration of the effect that we observed with the breast cancer cells; data not shown). The IGF axis is strongly associated with PCa, and IGFBP2 is an established mitogen and survival factor for PCa (Chatterjee et al 2004, Uzoh et al 2011 and has been reported to be associated with metabolic status (Heald et al 2006). IGFBP2 can act in both: an IGF-IR-dependent manner in PC3 cells and intrinsically (independent of IGF interaction) in DU145 cells (Uzoh et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…When we silenced FASN in the PCa cells, however, we found no reduction in the protective effect conferred by hyperglycaemia (in contrast to the amelioration of the effect that we observed with the breast cancer cells; data not shown). The IGF axis is strongly associated with PCa, and IGFBP2 is an established mitogen and survival factor for PCa (Chatterjee et al 2004, Uzoh et al 2011 and has been reported to be associated with metabolic status (Heald et al 2006). IGFBP2 can act in both: an IGF-IR-dependent manner in PC3 cells and intrinsically (independent of IGF interaction) in DU145 cells (Uzoh et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These include parameters of obesity and products released by adipose tissue, plasma insulin levels and insulin-like growth factors, liver enzymes, C-reactive protein and circulating metabolites, several components of circulating lipoproteins, microalbuminuria, and markers of increased cellular inflammation. [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] The status of these biomarkers as causative factors, either in generation of the metabolic syndrome or directly in atherogenesis, at present is uncertain. Some of them have been implicated as causes, but others as a reflection of a metabolic abnormality.…”
mentioning
confidence: 99%
“…25) Heald et al showed that a lower concentration of IGFBP2 in serum is a marker for elevating serum fasting glucose in patients with type 2 diabetes. 24) Therefore, these results suggest that lower IGFBP2 in serum might be influenced by lower IGFBP2 gene expression in the liver.…”
Section: Discussionmentioning
confidence: 82%
“…22,23) In particular, Nr4a3 and Adrb3 genes were involved in responses to stimulus (GO:50896), and Adiponectin genes were involved in lipid metabolism (GO:6629). Cluster 3 included the IGFBP2 gene, 24,25) however, there were no statistically overrepresented genes (more than 10 genes) within a specific GO term (pϽ0.01). Cluster 4 included the Pla2g7 26) gene, which was not assigned a GO term.…”
Section: Microarray Analysis Of Gene Expression Profiles In Diabetes-mentioning
confidence: 95%